2007
DOI: 10.1093/rheumatology/kem188
|View full text |Cite
|
Sign up to set email alerts
|

Is pre-assessment for anti-TNF therapy in RA necessary in the UK? Analysis of DAS28 in six centres

Abstract: The overwhelming majority of patients who fulfil eligibility criteria for anti-TNF drugs 1 month prior to baseline also fulfil the criteria at baseline. There is no significant change in the DAS28 over the month waiting to go onto anti-TNF therapy. A single assessment of the DAS28 would suffice to enable patients to go on to anti-TNF treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Also, the interpretation of the significance of the limits of agreement on the Bland–Altman plots is clinical rather than 2statistical, due to the distribution of the data collected. However, the range of DAS28 scores is comparable with those of Smith and colleagues (), who conducted a study with 679 patients examining the necessity of pre‐assessment for anti‐TNF therapy. This indicates that the results are generalizable to other patients attending biologic clinics.…”
Section: Discussionsupporting
confidence: 75%
“…Also, the interpretation of the significance of the limits of agreement on the Bland–Altman plots is clinical rather than 2statistical, due to the distribution of the data collected. However, the range of DAS28 scores is comparable with those of Smith and colleagues (), who conducted a study with 679 patients examining the necessity of pre‐assessment for anti‐TNF therapy. This indicates that the results are generalizable to other patients attending biologic clinics.…”
Section: Discussionsupporting
confidence: 75%
“…The problems inherent in a DAS28 score are well known but all four components (28 swollen and tender joint count, CRP/ESR, VAS score) used to derive the score show high correlations in individual patients (Smith et al, ). The BSR concluded that the DAS28 performs well with training, achieving good agreement among observers, and recommends that all secondary care departments should establish training programmes for specialist nurses and trainees that incorporate reliability assessments for joint counts and DAS28 calculation (Luqmani et al, ).…”
Section: Recommendations For Training and Standardizationmentioning
confidence: 99%